Ultrasound of Primary Aneurysmal Bone Cyst - Katrina N. Glazebrook; Gary L. Keeney; Michael G. Rock (Case Reports in Radiology)
Aneurysmal bone cysts (ABC) are rare, benign, expansile lesions of bone often found in the metaphyses of long bones in pediatric and young adult population. Multiple fluid levels are typically seen on imaging with magnetic resonance imaging (MRI) or computed tomography (CT). We describe a case of a primary ABC in the fibula of a 34-year-old man diagnosed on ultrasound with a mobile fluid level demonstrated sonographically.